2020
DOI: 10.3390/ijms21228545
|View full text |Cite
|
Sign up to set email alerts
|

PIMT Binding to C-Terminal Ala459 of CAIX Is Involved in Inside-Out Signaling Necessary for Its Catalytic Activity

Abstract: Human carbonic anhydrase IX (CAIX), a unique member of the α carbonic anhydrase family, is a transmembrane glycoprotein with high enzymatic activity by which CAIX contributes to tumorigenesis through pH regulation. Due to its aberrant expression, CAIX is considered to be a marker of tumor hypoxia and a poor prognostic factor of several human cancers. Hypoxia-activated catalytic function of CAIX is dependent on posttranslational modification of its short intracellular domain. In this work, we have identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…At the functional level, CAIX is activated by a hypoxia-induced increase of cAMP level and a subsequent activation of protein kinase A (PKA) that phosphorylates Thr443 in the IC [50]. Simko et al (2020) described a new role of the PIMT protein, which interacts with a methyl group in the amino acid alanine in the IC of CAIX, whilst a disruption of this interaction led to perturbations in CAIX-mediated pH regulation [51]. This finding indicates a possible new mechanism of the regulation of CAIX enzymatic activity.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…At the functional level, CAIX is activated by a hypoxia-induced increase of cAMP level and a subsequent activation of protein kinase A (PKA) that phosphorylates Thr443 in the IC [50]. Simko et al (2020) described a new role of the PIMT protein, which interacts with a methyl group in the amino acid alanine in the IC of CAIX, whilst a disruption of this interaction led to perturbations in CAIX-mediated pH regulation [51]. This finding indicates a possible new mechanism of the regulation of CAIX enzymatic activity.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…PIMT as a new interaction partner of CAIX. Recently discovered interaction partner of CAIX is the protein PIMT (protein-L-isoaspartyl methyltransferase), whose interac-tion was found through proteomic analysis and subsequently proven by immunoprecipitation [51]. PIMT is well known for its protein repair function, it regulates e.g.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural modification and development of novel small-molecule- or monoclonal-antibody-based compounds, with affinity and selectivity towards tumor-specific receptors/markers, belong to the most prospective approaches in the diagnosis, imaging, and therapy of hypoxic tumors, and so for personalized care of oncological patients [ 5 ]. Thus, a mechanism of the catalytic activity of tumor-associated hCA isozymes in hypoxic tumors and its inhibition has been a promising target over a long period in many studies by Supuran [ 6 , 7 , 8 , 9 ], Pastorek and Pastorekova [ 10 , 11 , 12 , 13 ] working groups and in other very recently published papers [ 14 , 15 , 16 , 17 , 18 ]. Anyway, considering a broader extent of disease (also involving non-oncological ones), the inhibition of other hCA isozymes is also useful, e.g., hCA I is related to retinal and cerebral edema, hCA II to glaucoma, bone and renal diseases, edema, epilepsy, or acute high-altitude illness, and hCA IV to glaucoma, stroke, and retinitis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular domain and its dynamics, including the cleavage and shedding of the PG domain observed by the authors, could have physiological relevance in the role of CAIX in cancer progression. Simko et al [8] highlighted the C-terminal Ala459 residue as an essential element for the catalytic activity of CAIX and showed that a structural change at the 459 position decreases the CA enzymatic activity. Moreover, the authors demonstrated the intracellular interaction of CAIX with the cytoplasmic protein PIMT, known for its protein repair function, and identified the Ala459 residues as a mediator of this interaction.…”
mentioning
confidence: 99%